2020
DOI: 10.1177/0031512520983082
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behavior of Brazilian College Students: Influences of Lifestyle, Negative Affectivity, and Personal Characteristics

Abstract: In this study we proposed to estimate the impact of lifestyle, negative affectivity, and college students’ personal characteristics on eating behavior. We aimed to verify that negative affectivity moderates the relationship between lifestyle and eating behavior. We assessed eating behaviors of cognitive restraint (CR), uncontrolled eating (UE), and emotional eating (EE)) with the Three-Factor Eating Questionnaire-18. We assessed lifestyle with the Individual Lifestyle Profile, and we assessed negative affectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
0
14
0
4
Order By: Relevance
“…Este achado reforça a ideia de que é adequado mensurar a afetividade negativa como um único constructo formado pelos sintomas de depressão, ansiedade e estresse. Martins et al (2019), Campos et al (2020) e Martins et al (2021) realizaram análises semelhantes, nas quais os autores avaliam o constructo afetividade negativa como um elemento formado pelos constructos depressão, ansiedade e estresse. Desse modo, no modelo estrutural final, será calculada a variável latente afetividade negativa a partir dos constructos depressão, ansiedade e estresse.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Este achado reforça a ideia de que é adequado mensurar a afetividade negativa como um único constructo formado pelos sintomas de depressão, ansiedade e estresse. Martins et al (2019), Campos et al (2020) e Martins et al (2021) realizaram análises semelhantes, nas quais os autores avaliam o constructo afetividade negativa como um elemento formado pelos constructos depressão, ansiedade e estresse. Desse modo, no modelo estrutural final, será calculada a variável latente afetividade negativa a partir dos constructos depressão, ansiedade e estresse.…”
Section: Resultsunclassified
“…Sugere-se que a intenção de abandono sofre influência direta da atitude (H1), da norma subjetiva (H2), do controle comportamental percebido (H3) e da afetividade negativa (H4). A afetividade negativa nesta pesquisa é avaliada a partir de sintomas de depressão, ansiedade e estresse, conforme sugere a literatura (Martins et al, 2019;Martins et al, 2021;Campos et al, 2020).…”
Section: Afetividade Negativa E O Contexto Universitáriounclassified
“…Corroborating our findings, the literature (Clarke & Best, 2017, 2019; Jallinoja, Niva, Helakorpi, & Kahma, 2014; Wardle et al, 2004) demonstrates that diet can be seen by dieters as effective for losing weight and promoting health. However, the practice of diets, especially restrictive ones, can negatively influence people's life (Franchi, 2012) and explain the greater importance placed on mood and convenience, since dieters can choose foods to control their emotions (Martins, da Silva, Maroco, & Campos, 2021). Unlike our study, Clarke and Best (2019) showed that dieters did not see the time and effort involved in preparing meals as barriers to choosing foods.…”
Section: Discussionmentioning
confidence: 99%
“…According to Prescott (2017), emotions are powerful drivers of behaviors and are key in promoting preferences, in particular those related to sensory characteristics of foods (e.g., odors and flavors). Individuals with a higher BMI could choose to eat highly palatable foods or the best‐known ones to regulate their emotions (Gibson, 2006; Martins et al, 2021). Furthermore, as global guidelines encourage weight loss to promote health (World Health Organization, 2020), individuals with obesity may experience social pressure to choose foods that achieve this goal.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of depression, anxiety and stress have been worked on in the literature as negative affectivity (Martins et al, 2019;Martins et al, 2021;Campos et al, 2020). Watson and Clark (1984) suggest that negative affectivity can be explained as a state in which an individual develops negative feelings and emotions.…”
Section: Introductionmentioning
confidence: 99%